Choice of specialized food products for children with cystic fibrosis who underwent critical conditions at an early age - Yu. S. Pinegina (Лечащий Врач, 2021)
The article is devoted to the choice of nutritional support in children with cystic fibrosis. Timely early diagnosis of cystic fibrosis, replacement therapy with microspherical pancreatic enzymes and adequate nutritional support prevent the development of protein-energy malnutrition. A wide range of specialized food products on the market allows you to choose the optimal correction method. The main requirements for the nutritional components introduced into the child’s diet are high calorie content, ease of absorption, anti-inflammatory and immunomodulating effect on the mucous membrane of the gastrointestinal tract. The results of the use of specialized nutrition for cystic fibrosis at the stage of recovery of children with protein-energy deficiency are presented. In the State Novosibirsk Regional Clinical Hospital (Novosibirsk), as part of complex therapy in children of the first year of life suffering from cystic fibrosis, a specialized product of children’s dietary food was used. On the basis of the children’s pulmonology department of the clinic, 8 children with this pathology were treated with the use of a therapeutic mixture during the recovery period from 12 to 180 days. It was shown that during the use of the therapeutic mixture, patients achieved good results, all children had a good appetite and stable weight gain.